Switching Dynamics and the Stress Process. (June 2013) - Cornwell, Benjamin
This article shows how maintaining social relationships can be a daily hassle that has implications for the stress process, depending on how often individuals transition, or "switch, " between various social roles and social settings throughout the day. I use nationally representative time-diary data on 7, 662 respondents from the 2010 American Time Use Survey to measure individual rates of switching behavior and to examine how it relates to perceived stress. Regression analysis shows that net of how many social roles they play and settings they visit on a given day, individuals who switch more frequently between these elements report higher levels of stress. This finding holds for women but not men, suggesting that switching dynamics are disproportionately stressful for women. I close by discussing the implications of the findings for research on gender and health.